Analisis Pengaruh Pembiayaan Syariah dan Variabel Makro Ekonomi Terhadap Ekspor Indonesia (Studi Pada BUS Devisa dan LPEI) - Rizky Rahmawati; Djoni Djatnika (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research aims to determine the effect of financing channeled by Foreign Exchange Islamic Bank, LPEI sharia financing, inflation and exchange rates simultaneously and partially on Indonesian exports in 2015 - 2019. The sampling technique in this research is purposive sampling method and used secondary data from Bank Indonesia, BPS, OJK and the financial statements of each bank. The research used quantitative method. Data analysis techniques used is multiple linear regression ordinary least Square (OLS) using software Eviews 9. The results of this research indicate that simultaneously the financing channeled by Foreign Exchange Islamic Bank, LPEI sharia financing, inflation and exchange rates have a significant effect on Indonesian exports. Partially the financing channeled by foreign exchange Islamic Bank and inflation does not affect on Indonesian exports. LPEI sharia financing and exchange rates has a significant positive effect on Indonesian exports.